Het kantoorgebouw van het electriciteitsgebouw te Rotterdam (Bulletin KNOB, 1990)
The office building of the Municipal Electricity Service at Rotterdam is the first concrete working-out of the Dutch striving after multi-storey buildings and framed constructions in particular. Since the building will lose its original function this article makes researches into the meaning of this office to Rotterdam's history of modern architecture and town-planning in the period 1920-'40.From 1907 on several plans have been conceived to provide the Electricity Service with a suitable housing. The municipal regulation prohibited the proposal (1919) to construct a multi-storey building in the historical centre. The design for a five-storey building with annexes (1923) inspired Burgomaster and Aldermen to agree with the erection of a new office building elsewhere in town.A proposal of director H.H. Ehrenburg to utilize a site on the Rochussenstreet, which offered excellent conditions to multi-storey building both and a good situation with respect to the centre finally was chosen as most suitable site to build the new office. This new location formed part of the plan for extension by Ir. W. G. Witteveen.The plan occupied a transitional area between the old and the new town destined to erect all sorts of public buildings. Witteveen planned the office building of the Electricity Service as a striking 'skyscraper' to close the development of this area. The official map (1926) already represents the suggested shape of the building. The design served as a model to the series of office buildings on the Rochussenstreet's southern side as well.Architect Johannes Poot of the Building Department of Municipal Works (Witteveen was head of this department) was charged with the construction of the new office in 1926. Both municipality and town council chose a fast way of construction by means of the American steel-skeleton system. The plan as presented to the town council shows two separated building blocks. The administrative section housed in a multi-storey building with eleven floors and the strongly horizontal storehouse comprised five floors with a total height of 21 metres.Witteveen's study tour to Cologne where he had a look at the 'Hochhaus' by J. Koerfer (1924-25) and American examples of skyscrapers reaching Europe in architectural reviews gave rise to the construction of the skeleton in concrete instead of steel. The specification of 1928 shows more constructive unity by an equal articulation of both main buildings. The definitive plan of 1929 enheightens the tower with two floors. Walls and supports have been worked up with natural stone and metal.On the 14th of September 1931 the - at the time extremely expensive - new office building for the Municipal Electricity Service could be put into use officially. In the years after delivery the importance of the building certainly was being recognized. Although building techniques in Holland were not developed as far as elsewhere in Europe Witteveen and Poot succeeded in the realization of a building with modern construction- methods. Lines of demarcation with later representatives of the architectural trend of New Building can hardly be drawn.